2012
DOI: 10.1097/ana.0b013e318235af18
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Agmatine After Focal Cerebral Ischemia in Diabetic Rats

Abstract: AGM posttreatment reduced cerebral infarct size and neurological deficit expression in diabetic rats subjected to MCAO. The reduced infarct size was associated with a decrease in apoptosis and NOS expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The results on the effect of SES on nitrosative stress induced by nitric oxide and reactive nitrogen oxide species are also in agreement with other reports (Cui et al, 2012;Iadecola et al, 1997;Koh, 2012). The inducible isoform of NOS (iNOS) is expressed in response to inflammatory process in cells, and thus, it is well appreciated that iNOS produces neurotoxic NO that causes neuronal cell death and exacerbates glutamate toxicity after cerebral ischemia (Cui et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results on the effect of SES on nitrosative stress induced by nitric oxide and reactive nitrogen oxide species are also in agreement with other reports (Cui et al, 2012;Iadecola et al, 1997;Koh, 2012). The inducible isoform of NOS (iNOS) is expressed in response to inflammatory process in cells, and thus, it is well appreciated that iNOS produces neurotoxic NO that causes neuronal cell death and exacerbates glutamate toxicity after cerebral ischemia (Cui et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…The inducible isoform of NOS (iNOS) is expressed in response to inflammatory process in cells, and thus, it is well appreciated that iNOS produces neurotoxic NO that causes neuronal cell death and exacerbates glutamate toxicity after cerebral ischemia (Cui et al, 2012). However, inhibition of iNOS in cerebral ischemia was reported to improve neurological deficits, reduces infarct volume, and reduces sensitivity to focal cerebral ischemia (Iadecola et al, 1997;Koh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For protein extraction, tissues were homogenized as previously described (Cui et al, 2012). Cell homogenates were centrifuged at 13,000g for 15 minutes at 4°C.…”
Section: Western Immunoblotsmentioning
confidence: 99%
“…In present study, DHA treatment reduced the expression of Bax and caspase-3 which is the marker of the mitochondrial cell death and iNOS in ischemic injured brain. Nitric oxide (NO) that causes neuronal cell death and exacerbates glutamate toxicity after cerebral ischemia [68] is synthesized by NO synthase such as iNOS [69]. Several studies demonstrated that inhibition of iNOS in cerebral ischemia improves neurological deficits and reduces infarct volume [70,71].…”
Section: Discussionmentioning
confidence: 99%